Factors for Chinese Students Choosing Australian Higher Education and Motivation for Returning: A Systematic Review. (May 2019) - Zhai, Keyu; Gao, Xing; Wang, Geng
Under the third wave of international student mobility, Australia has become the third largest country receiving international students. Compared with the United States and the United Kingdom, Australia can still maintain a stable increase in terms of hosting Chinese students. For Australia, attracting international students becomes an important part of Australian universities' business and cultural diversity. This paper reports the Chinese students' initiations of choosing Australian higher education and motivations for returning, aiming at contributing to a more accurate and comprehensive understanding of Chinese students' international flows. By retrieving all relevant literature published from 2000 to 2017, this paper engages with a systematic review to provide an overview of what exactly motivates Chinese students choosing Australian higher education and returning. Based on the robust assessment criteria, we selected 68 articles for analysis, and according to the coding results, we developed four themes influencing Chinese students' choice of Australia, including academic requirement and attainment, employment and future career prospects, host country environment, and social connections and three themes for returning: emotional needs, culture and integration in Australia, and career opportunities in China. The research results contribute to policy implications for Australian international higher education development.